Ability beliefs: Why believing in your ability matters in self-regulated language learning - Nakata, Yoshiyuki; Takeuchi, Osamu; McEown, Maya Sugita (Studies in Second Language Learning and Teaching, 2025)
The key to successful language learning depends on the extent to which learners are self-regulated in learning a second or foreign language (L2). In this process, learners’ perceptions and beliefs about their abilities play a crucial role in predicting or controlling positive or negative emotions, motivation and the use of strategies. Therefore, it is vital to clarify the role that learners’ perceived abilities play in self-regulated language learning. The present paper aims to: (1) provide a review of empirical studies related to L2 strategy use, motivation, and social regulation about ability beliefs, (2) explore the reciprocal relationship between these constructs, and (3) suggest future research directions that will help promote self-regulated language learning research. By doing so, we aim to contribute to the broadening of L2 proficiency research, provide a more comprehensive understanding of the second language acquisition process, and ultimately support language teachers in understanding the developmental processes of L2 learners.